2022
DOI: 10.1186/s12916-022-02312-5
|View full text |Cite
|
Sign up to set email alerts
|

Human serum from SARS-CoV-2-vaccinated and COVID-19 patients shows reduced binding to the RBD of SARS-CoV-2 Omicron variant

Abstract: Background The COVID-19 pandemic is caused by the betacoronavirus SARS-CoV-2. In November 2021, the Omicron variant was discovered and immediately classified as a variant of concern (VOC), since it shows substantially more mutations in the spike protein than any previous variant, especially in the receptor-binding domain (RBD). We analyzed the binding of the Omicron RBD to the human angiotensin-converting enzyme-2 receptor (ACE2) and the ability of human sera from COVID-19 patients or vaccinees… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
63
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 57 publications
11
63
2
Order By: Relevance
“…We then analysed the binding affinity of BA.2 S receptor binding domain (RBD) to ACE2 by an yeast surface display assay 16,22,24 . Although the binding affinity of BA.1 S RBD to ACE2 is controversial 11,[15][16][17]25,26 , our yeast surface display showed that the binding affinity of the RBD of BA.1 and BA.2 is comparable (Extended Data Fig. 6b).…”
Section: Virological Features Of Ba2 In Vitromentioning
confidence: 85%
“…We then analysed the binding affinity of BA.2 S receptor binding domain (RBD) to ACE2 by an yeast surface display assay 16,22,24 . Although the binding affinity of BA.1 S RBD to ACE2 is controversial 11,[15][16][17]25,26 , our yeast surface display showed that the binding affinity of the RBD of BA.1 and BA.2 is comparable (Extended Data Fig. 6b).…”
Section: Virological Features Of Ba2 In Vitromentioning
confidence: 85%
“…The RBD and spike ectodomain (S1 + S2, referred as S) sequence of the Omicron variant was ordered as GeneString from GeneArt (Thermo Fisher) according to EPI_ISL_6590608 (partial RBD Sanger sequencing from Hong Kong), EPI_ISL_6640916, EPI_ISL_6640919 and EPI_ISL_6640917 including Q493K which was corrected later to Q493R. All sequences of the RBD (319-541 aa of GenBank: MN908947) and spike ectodomain (14-1208 aa of GenBank: MN908947 with proline substitutions at positions 986 and 987 and “GSAS” substitution at the furin site, residues 682–685) of G614 and Omicron BA.1 were inserted in a NcoI/NotI compatible variant of the OpiE2 expression vector containing an N-terminal signal peptide of the mouse Ig heavy chain and a C-terminal 6xHis-tag 50 . RBD of G614, Beta, Delta and Omicron and S of G614 and Omicron BA.1 were expressed baculovirus-free in High Five insect cells and purified on HisTrap excel columns (Cytiva) followed by preparative size exclusion chromatography on 16/600 Superdex 200 pg columns (Cytiva) 51 , 52 .…”
Section: Methodsmentioning
confidence: 99%
“… 32 The binding affinity of human ACE2 receptor and RBD of Omicron and other VOCs was analyzed to show that ACE‐2 binding affinity to the RBD was lower in Omicron as compared to Beta and Delta variants indicating that receptor binding affinity is not driving omicron evolution. 35 Rather, significant reduction in antibody titers against the Omicron RBD as compared to ancestral SARS‐CoV‐2 RBD suggest that neutralizing antibodies play an important role in the immune escape shown by Omicron.…”
Section: Mutational Landscape Of Omicron Variantmentioning
confidence: 98%